PENINGKATAN KETERAMPILAN PESERTA DIDIK PADA KOMPETENSI DASAR PENATAAN PRODUK MELALUI MEDIA WHATSAPP - Teti Sumiyati (PREDIKSI (PROFESI PENDIDIKAN INDONESIA), 2022)
This research is entitled "Improving Student Skills in Basic Competencies of Product Arrangement Through Whatsapp Media in Class XII Commerce Administration 1 SMK Negeri 1 Rangkasbitung". This Study to manage the planning and activities of student in product arrangement learning in applying WhatsApp media and improve the skills of students. The method in this study used a classroom action research which was carried out in a participatory manner. The research activity was carried out at the State Vocational High School 1 Rangkasbitung, especially in class XII Marketing Online Business 1. The subjects in this study were class XII Markeing Online Business 1 SMK Negeri 1 Rangkasbitung with a total of 36 students. Data collection was carried out on each student activity and situation related to the research action carried out, namely through observation, interviews and performance. In accordance with the type of data collected, there are two data techniques used, namely quantitative and qualitative analysis. Quantitative analysis is used to analyze the results and qualitative analysis is used to observe the results of students and teachers. The results of this study indicate an increase in the skills of students who have exceeded the KKM that has been set at 80.00, namely from the initial condition before the action the average skill value of 67.63 increased to 75.92 in the first cycle and increased to 82.24 in the second cycle.